2015
DOI: 10.1093/femsec/fiv128
|View full text |Cite
|
Sign up to set email alerts
|

The microbiome ofFolsomia candida: an assessment of bacterial diversity in aWolbachia-containing animal

Abstract: The springtail Folsomia candida is an important model organism for soil ecology, ecotoxicology and ecogenomics. The decomposer activities of soil invertebrates like Folsomia depend on their relationship with microbial communities including gut symbionts. In this paper, we apply high-throughput sequencing to provide a detailed characterization of the bacterial community associated with parthenogenetic F. candida. First, we evaluated a method to suppress the amplification of DNA from the endosymbiont Wolbachia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 43 publications
3
40
1
Order By: Relevance
“…A detailed characterization of the microbiome of F. candida has recently been reported, enabling further studies on interactions between its beta‐lactam genes and the bacterial community in the gut (Agamennone et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…A detailed characterization of the microbiome of F. candida has recently been reported, enabling further studies on interactions between its beta‐lactam genes and the bacterial community in the gut (Agamennone et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…A previous study based on cloning and 16S rRNA gene sequencing isolated 95 clones from the springtail, 83 of which (87%) were identified as Bacillus weihenstephaniensis Lechner et al (Czarnetzki & Tebbe, 2004). Agamennone et al (2015) also indicated that members of the B. cereus group are among the dominant groups in F. candida microbiome, representing 4% of the reads in a natural population of springtails. However, the limited resolution of 16S rRNA in this clade did not allow for a more specific identification within this clade.…”
Section: Discussionmentioning
confidence: 99%
“…Agamennone et al. () also indicated that members of the B. cereus group are among the dominant groups in F. candida microbiome, representing 4% of the reads in a natural population of springtails. However, the limited resolution of 16S rRNA in this clade did not allow for a more specific identification within this clade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The host’s genome contains biosynthetic gene clusters for secondary metabolites, such as for β-lactams (2), which are induced in the gut epithelium upon stress (3). Previous amplicon-sequencing studies (4, 5) revealed the prominence of B. cereus in the F. candida midgut. An association between the propagation cycle of members of the B. cereus clade and the internal environment of animals has been suggested (6, 7).…”
Section: Genome Announcementmentioning
confidence: 94%